NoxO1 Determines the Level of ROS Formation by the Nox1-Centered NADPH Oxidase - Dana Maureen Hebchen; Manuela Spaeth; Niklas Müller; Katrin Schröder (Antioxidants, 2024)
The Nox1-centered NADPH oxidase complex facilitates the transfer of electrons from intracellular NADPH across the cell membrane to extracellular molecular oxygen, resulting in the formation of superoxide. The complex is comprised of two membrane-bound subunits, namely Nox1 and p22phox, and the cytosolic subunits, namely NoxA1 and NoxO1. The presence of NoxO1 facilitates the proximity of all components, thereby enabling the complex to exhibit constitutive activity. Despite the theoretical sufficiency of all subunits in a 1:1 ratio, the precise composition of the Nox1-centered NADPH oxidase remains unknown. Analyses of mRNA expression in different cell lines revealed an unequal expression of the components, with an excess of NoxO1. Furthermore, plasmid-based overexpression of individual components of the Nox1-centered NADPH oxidase resulted in an excess of NoxO1 mRNA. The objective of this study was to analyze the ability of NoxO1 to control the level of ROS formation by the Nox1 complex. To this end, we generated Hek293 cells for constitutive expression of Nox1 and NoxA1, which were then transfected with increasing concentrations of NoxO1. The data presented herein suggests that ROS formation by the Nox1-centered NADPH oxidase is dependent on the concentration of NoxO1. A surplus of NoxO1 has been observed to exert control over the activity of the complex in accordance with a dose-dependent mechanism. We thus conclude that the ratio of Nox1, NoxA1, and NoxO1 complexes does not adhere to a 1:1 ratio. Conversely, the availability of NoxO1 serves to regulate the formation of ROS by the Nox1-centered NADPH oxidase.